LOYALITAS KONSUMEN - Yuni Istanto (UMSurabaya Publishing, 2007)
Industrial organizations which a mature stage, which deal with the limited prospects in keeping a high development number (Jarvis &Mayo, 1986) look for a way which they can use to prevent their market. One of the strategies which is identified has a connection with the consumen-supplier relation concept, in which the loyality programs are considered as the most important aspect (Palmer, 1994) In adopting the loyality programs, the companiy’s main focus is not for getting new consumens, but for getting the remained consumens’s loyality, and in the end, for increasing the relation of supplier and consumens (Zeitham/Bitner, 1996). This study discuss the definition, usage & loyality dimention.